Answer :

Given equation: 15 (x – 1) + 4 (x + 3) = 2 (7 + x)

⇒ 15x – 15 + 4x + 12 = 14 + 2x (Removing brackets)

15x + 4x – 15 + 12 = 14 + 2x

19x – 3 = 14 + 2x

⇒ 19x – 2x = 14 + 3 (Transposing 2x to LHS and 3 to RHS)

17x = 17

⇒ x = (Transposing 17 to RHS)

x = 1

∴ The solution of 15 (x – 1) + 4 (x + 3) = 2 (7 + x) is

x = 1.

Rate this question :

How useful is this solution?

We strive to provide quality solutions. Please rate us to serve you better.

Related Videos

NCERT | Imp. Questions on Solutions of Linear Equations in One Variable39 mins

NCERT | Linear Equations in One Variable44 mins

Making Equations Simple41 mins

Foundation | Cracking Previous Years IMO Questions42 mins

Solution of Linear Equation34 mins

NCERT | Solving Imp. Qs. Related to Ages49 mins

Applications of Linear Equations in One Variable37 mins

Linear Equation in One Variable46 mins

Champ Quiz | Linear Equation in One Variable44 mins

NCERT - Imp. Qs. Discussion From Linear Equation in One Variable45 mins

Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Expertsview all courses

Dedicated counsellor for each student

24X7 Doubt Resolution

Daily Report Card

Detailed Performance Evaluation

RELATED QUESTIONS :

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics